2003
DOI: 10.2337/diabetes.52.5.1215
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Prekallikrein

Abstract: The relevance and significance of the plasma kallikrein/ kinin system as a risk factor for the development of vascular complications in diabetic patients was explored in a cross-sectional study. We measured the circulating levels of plasma prekallikrein (PK) activity, factor XII, and high؊molecular weight kininogen in the plasma of 636 type 1 diabetic patients from the Diabetes Control and Complications Trial/Epidemiology and Diabetes Intervention and Complications Study cohort. The findings demonstrated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
2
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 48 publications
6
48
2
1
Order By: Relevance
“…This may also suggest that high levels of tissue kallikrein in diabetic patients might be a predisposing factor in the induction of type 2 diabetes due to the inhibition of glucose transfer to the tissues [38]. Plasma levels of tissue kallikrein have been reported to be increased in type 2 diabetes as previously reported [39,40]. In the present study however, we also observed high concentrations of plasma tissue kallikrein, which presumably be due to the hyperactivity of the BK-forming system to induce systemic metabolic abnormalities.…”
Section: The Bradykinin System and Diabetessupporting
confidence: 67%
“…This may also suggest that high levels of tissue kallikrein in diabetic patients might be a predisposing factor in the induction of type 2 diabetes due to the inhibition of glucose transfer to the tissues [38]. Plasma levels of tissue kallikrein have been reported to be increased in type 2 diabetes as previously reported [39,40]. In the present study however, we also observed high concentrations of plasma tissue kallikrein, which presumably be due to the hyperactivity of the BK-forming system to induce systemic metabolic abnormalities.…”
Section: The Bradykinin System and Diabetessupporting
confidence: 67%
“…Acute administration of aprotinin, a kallikrein inhibitor, and/or B2R antagonist in these hyper filtering diabetic rats reduced the GFR and RPF [11,12] These findings may suggest that the high levels of renal tissue kallikrein and BK may mediate renal hyper filtration in diabetes. There was no alteration in the creatinine levels in the present study; however, high plasma prekallikrein levels may suggest the onset of renal abnormalities .In fact, high plasma prekallikrein levels have been documented in type 1 diabetic patients [10]. These investigators suggested that increased plasma prekallikrein level could be a risk factor for hypertension and nephropathy in type 1 diabetes.…”
Section: Commentarycontrasting
confidence: 49%
“…BK is rapidly (< 15 sec) inactivated by circulating kinases [9]. BK acts on B1receptor (B1R) and B2 receptor (B2R) [10] to elicit physiological and pharmacological actions. It has been shown previously that type 1 diabetic patients are at a risk of developing nephropathy, having increased renal tissue kallikrein and BK levels [11].…”
Section: Commentarymentioning
confidence: 99%
“…The principal effectors of the two systems, angiotensin II and BK, exert opposing effects on vascular tone, with angiotensin II directly promoting VSMC contraction and BK indirectly causing vasodilation through BK receptor-mediated NO generation by vascular endothelial cells. Despite the generally salutary effects of BK, it is clear that dysregulation of the KKS is associated with progression of the vascular and renal complications of diabetes mellitus (40). In the setting of endothelial denudation, BK can act directly on B1 and B2 bradykinin receptors expressed by VSMC to promote vasoconstriction in a manner similar to angiotensin II (13).…”
Section: Discussionmentioning
confidence: 99%